Endovascular Management of a Traumatic Infraorbital Pseudoaneurysm Causing Orbital Compartment Syndrome. Issue 5 (September 2017) - Leung, Victoria C.; Hussain, Ahsen; Krings, Timo; DeAngelis, Dan
Abstract : An 89-year-old woman presented after blunt injury to the left orbit from a fall. Examination findings were suggestive of left-sided orbital compartment syndrome, unresponsive to emergent lateral canthotomy and cantholysis. CT revealed a left-sided orbital floor blowout fracture involving the infraorbital canal, with a large maxillary and infraorbital hematoma. Angiography revealed a pseudoaneurysm supplied by the infraorbital artery. Interventional neuroradiology successfully achieved hemorrhage control by endovascular obliteration of the parent artery close to the pseudoaneurysm. To our knowledge, this is the first reported case of successfully managing active intraorbital hemorrhage causing orbital compartment syndrome by endovascular vessel sacrifice of an infraorbital artery pseudoaneurysm. Abstract : Endovascular coiling can be performed to control hemorrhage from a traumatic infraorbital artery pseudoaneurysm causing orbital compartment syndrome.